SUBCUTANEOUS NADH IMPLANT IN THE MANAGEMENT OF CHRONIC FATIGUE SYNDROME: AN INTEGRATIVE REVIEW OF CLINICAL AND METABOLIC EVIDENCE - Viana, Valéria Goulart; Balderrama, Guilherme Tunckus; Correia, Isisnaldo Silva; de Melo, Giovanna Abe Rodrigues; Lopes Júnior, Marcelo de Araújo; de Morais, Lucas Emericiano; Bezerra, Bruna Bastos; Bezerra, Luisa Bastos; Cadete, Diego Quirino; Neri, Diegomaier Nunes; Barros, David de Sousa Cortez; dos Santos, Patrícia Lemos; et al. (Seven Editora, 2025)
This integrative review aimed to gather, analyze, and synthesize the available clinical, metabolic, and pharmacological evidence on the use of NADH in the management of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), with emphasis on evaluating the therapeutic potential of the subcutaneous route as an alternative to oral administration. The methodology followed the model proposed by Whittemore and Knafl (2005), complemented by the guidelines of Mendes, Silveira, and Galvão (2008), encompassing six structured stages. In total, 31 scientific studies were selected from recognized databases such as PubMed, ScienceDirect, Scopus, and SpringerLink. Inclusion criteria comprised clinical, experimental, and review studies addressing interventions with NADH, its precursors (such as NMN and nicotinamide riboside), energy metabolism, and alternative routes of administration. Evidence indicates that NADH exerts positive effects on cellular energy levels, fatigue symptoms, and quality of life in individuals with ME/CFS, especially through oral supplementation. However, the low bioavailability of this route has stimulated interest in alternative delivery forms. Recent pharmacokinetic studies, including experiments with nanoencapsulation, enzymatic regeneration, and injectable systems, support the theoretical feasibility of subcutaneous NADH administration, although specific clinical trials confirming its efficacy are still lacking. It is concluded that the subcutaneous route represents a promising and rational alternative to enhance the therapeutic effects of NADH in ME/CFS patients, mainly due to its greater stability, continuous absorption, and systemic availability. Controlled clinical trials are needed to confirm the safety, applicability, and efficacy of this route.DOI: https://doi.org/10.56238/sevened2025.037-023